Clinical features of Wilson disease - Stremmel, Wolfgang; Merle, Uta; Weiskirchen, Ralf (Annals of translational medicine, 2019)
Wilson disease (WD) presents often as a chameleon with a plethora of mild and discrete symptoms. As disease of young aged people, the clinical diagnosis is extremely difficult and misdiagnoses are frequent. Tremor, dysarthria and hepatomegaly sometimes suggest alcoholic liver disease which is a disaster for the patients. Due to the only moderate abnormality of liver function tests the disease is underestimated in its severity with a fatal prognosis when not adequately treated. Therefore, it is the challenge to consider WD as diagnosis, particularly in young patients with unclear liver disease, neuropsychiatric disorders or hemolysis.